Terra firma-forme dermatosis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
Terra firma-forme dermatosis was the term coined by Duncan et Al. (1) in 1987 to indicate a look of the skin reminiscent of dry land. A research on PUBMED shows only 7 reports published in the 23 subsequent years. However, in all the reports the dermatosis is referred as frequent, although not well known and underdiagnosed. It is also reported as source of useless fear in the parents and of complex and expensive examinations. This seeming contradiction can be explained when taking into account that only a few cases are observed by the specialist, whereas most cases are not observed by the general practitioner or are considered a trivial condition not deserving of consideration. Terra firma-forme dermatosis is characterized by brownish plaques of hyperkeratosis reminiscent of dirty skin. It occur in subjects who wash normally or excessively with water and soap. The lesions, on the other hand, can be removed thanks to strong rubbing with a gauze soaked in an alcoholic solution. This maneuver, which is both diagnostic and therapeutic, was accidentally discovered by the first Authors (1) who described the disorder. The latter affects subjects of any age, although it is more frequent in the first two decades. It usually occurs at the end of summertime (1, 2, 3) and affects mainly the neck, but also the trunk and limbs. Usually, the patient does not relapse after the first removal with alcohol. The cause of the disorder is not clear. However, the hyperpigmentation and thickening of the skin and its onset after sun exposure suggests the importance of the light. However, the lack of relapse in the following years probably involves other causal factors. The examinations aimed at unveiling particular microorganisms put only in evidence the presence in the affected skin of the normal saprophytic flora. The histological examination shows orthokeratotic hyperkeratosis with tendency to form areas of hyperkeratosis arranged in whorls, keratin globules in the thickened horny layer staining with toluidine blue, increas-ed melanin in the epidermis, moderate acanthosis, lack of significant inflammatory infiltrate in the dermis (1). These findings are compatible with a defective maturation of keratin (1).